Examining the impact of IT investment on insurer productivity: A bootstrapped Malmquist frontier analysis approach - YEW, Jee Yuen (Institutional Knowledge at Singapore Management University, 2020)
This paper attempts to examine productivity changes of insurance companies in Singapore as represented by bootstrapped Malmquist indices, generated from a data envelopment analysis (DEA)-based frontier analysis, and attribute these changes to an increasing investment in information technology infrastructure and equipment, and increasing investment in staff enhancement. Through this analysis, the author finds that there has been a general increase in productivity and efficiency from 2011 – 2017, as seen from changes in the kernel density functions of productivity change between the two periods. The author also finds, through running a panel tobit regression model, that there is a positive correlation between productivity change, and investments in IT equipment and staff enhancement. Admittedly, there are still limitations to the methodology used, in particular the lack of breakdown of IT investment data.